ANALISIS PENGARUH STORE ATMOSPHERE DAN SALES PROMOTION TERHADAP EMOTIONAL SHOPPING DAN IMPULSE BUYING BEHAVIOR - Ariani Darmayasa, Intan Agustina; Sukaatmadja, I Putu Gde (E-Jurnal Manajemen; Vol 6 No 11 (2017), 2017)
Impulse buying behavior is shopping behavior that consumer do without planning first. The purpose of this study was to determined the impact of store atmosphere and sales promotion to emotional shoping and impulse buying behavior. Purposive sampling technique is used for this study resulting in a sample of 108 people which is Indomaret consumers in the city of Denpasar. The impact of each variables to emotional shopping and impulse buying behavior are using SEM (Structural Equation Modeling) analysis technique with AMOS 18.00 progra. The result of this study are store atmosphere and sales promotion each of them has a positive impact and significant to emotional shopping and impulse buying. This study is also shows that emotional shopping has a positive and significant impact to impulse buying behavior.